Expression in Escherichia coli and function of Pseudomonas aeruginosa outer membrane porin protein F. - Woodruff, W A (1986)
The gene encoding porin protein F of Pseudomonas aeruginosa was cloned onto a cosmid vector into Escherichia coli. Protein F was expressed as the predominant outer membrane protein in a porin-deficient E. coli background and was clearly visible on one-dimensional sodium dodecyl sulfate-polyacrylamide gels in a porin-sufficient background. The identity of the protein F from the E. coli clone and native P. aeruginosa protein F was demonstrated by their identical mobilities on sodium dodecyl sulfate-polyacrylamide gel electrophoretograms, 2-mercaptoethanol modifiabilities, and reactivities with monoclonal antibodies specific of two separate epitopes of protein F. In the course of gene subcloning, a 2-kilobase DNA fragment was isolated, with an apparent truncation of the part of the gene encoding the carboxy terminus of protein F. This subclone produced a 24,000-molecular-weight, outer membrane-associated, truncated protein F derivative which was not 2-mercaptoethanol modifiable and which reacted with only one of the two classes of protein F-specific monoclonal antibodies. The 2-kilobase fragment was used in Southern blot hybridizations to construct a restriction map of the cloned and subcloned fragments and to demonstrate with restriction digests of whole P. aeruginosa DNA that only one copy of the protein F gene was present in the P. aeruginosa chromosome. The protein F produced by the original cosmid clone in a porin-deficient E. coli background was purified. To demonstrate retention of porin function after cloning, the protein F from the E. coli clone was incorporated into black lipid bilayer membranes. Two major classes of channels were revealed. The predominant class of channels had an average conductance of 0.36 nS in 1 M KCl, whereas larger channels (4 to 7 nS) were seen at a lower frequency. Similar channel sizes were observed for porin protein F purified by the same method from P. aeruginosa outer membranes.